SOCIAL SUPPORT AND BREAST INTERCURRENCES IN NURSING MOTHERS WHO BREASTFEED EXCLUSIVELY - Francyleia Abreu da Silva; Nayra Anielly Cabral Cantanhede; Poliana Cristina de Almeida Fonseca; Sueli Ismael Oliveira da Conceição (Universidade do Estado do Rio de Janeiro, 2019)
Objective: To evaluate the association between spouse and family support to nursing mothers assisted in a Puericulture Program in a Human Milk Bank and breast intercurrences during the period of exclusive breastfeeding (EBF). Methods: Cross-sectional study with 169 nursing mothers assisted by the Puericulture Program of a Human Bank Milk in São Luís-MA. A semi-structured questionnaire was administered to collect socioeconomic and demographic data, information on prenatal conditions, social support, and breast intercurrences. Chi-Squared Test and Fischer's Exact Test were employed to verify the associations between the covariables and the pertinent outcome (p<0.05). Results: All of the nursing mothers received prenatal care (100%), from which 81.3% had six or more visits, mostly in the public health system (94.7%). More than half of the nursing mothers did not receive orientation on breastfeeding (55.4%), infant's position to breastfeed (63.7%), and breast care during prenatal care (59.2%). Approximately 82% received partner support. However, when suffering from nipple pain (41.1%) and in case of absent, flat or inverted nipples (13.2%), most mothers (86.8%) did not receive such support during EBF (p=0.021). Conclusion: There was considerable social support towards the nursing mothers, but most of those that presented breast intercurrences did not receive any support. It is important to emphasize the need for greater participation of the actors that constitute the social network of pregnant women during prenatal care and child heath care. DOI: 10.12957/demetra.2019.43824